Propolis supplementation on inflammatory and oxidative stress biomarkers in adults: a systematic review and meta-analysis of randomized controlled trials - Bahari, Hossein; Shahraki Jazinaki, Mostafa; Aliakbarian, Mohsen; Rashidmayvan, Mohammad; Golafrouz, Haniyeh; Rahnama, Iman; Khodashahi, Rozita; Malekahmadi, Mahsa (Frontiers in Nutrition, 2025)
BackgroundAlthough a large number of trials have observed the anti-inflammatory properties of propolis, the currently available research remains controversial regarding its beneficial health effects. Hence, the purpose of this study was to examine the effect of propolis on inflammatory and oxidative stress markers in adults.MethodsA comprehensive search was performed in Scopus, Web of Science, and PubMed/Medline to find relevant randomized controlled trials (RCTs) until January 2024. The overall effect sizes were calculated using the random-effects model and expressed as weighted mean differences (WMD) with a 95% confidence interval (CI). The possible heterogeneity between included trials was assessed by performing Cochran’s Q test.ResultsIn total, 27 trials with 29 treatment arms were eligible for inclusion in this review. This meta-analysis revealed that propolis consumption led to a significant decrease in C-reactive protein (CRP) (WMD: –1.23; 95%CI: –1.76, –0.69; p < 0.001), Interleukin-6 (IL-6) (WMD: –1.52; 95%CI: –2.10, –0.93; p < 0.001), Tumor necrosis factor-α (WMD: –1.15; 95%CI: –1.75, –0.55; p < 0.001), and Monocyte chemoattractant protein-1 (MCP-1) (WMD: –35.33; 95%CI: –50.28, –20.37; p < 0.001), and a significant increase in total antioxidant capacity (TAC) (WMD: 0.32; 95%CI: 0.12, 0.51; p = 0.001), Glutathione (GSH) (WMD: 4.71; 95%CI: 3.17, 6.25; p < 0.001), and Glutathione peroxidase (GPx) (WMD: 44.75; 95%CI: 5.10, 84.40; p = 0.02). However, there were no significant effects on IL-10, IL-2, IL-8, pro-oxidant-antioxidant balance (PAB), malondialdehyde (MDA), and superoxide dismutase (SOD) in comparison to the control group.ConclusionPropolis supplementation appears effective in reducing inflammation and oxidative stress by enhancing antioxidant capacity and reducing specific inflammatory markers. However, variations in study designs, dosages, and participant characteristics contribute to the heterogeneity of results. Further well-designed RCTs are needed to confirm these findings and determine the optimal dosage and long-term effects. Given its potential anti-inflammatory and antioxidant properties, propolis may serve as a complementary approach in managing inflammation-related conditions, though its clinical application requires further validation.Systematic review registrationhttps://clinicaltrials.gov/, identifier CRD42023474033.